Degradome analysis to identify direct protein substrates of small-molecule degraders - Jochem, Marco; Schrempf, Anna; Wagner, Lina-Marie; Segal, Dmitri; Cisneros, Jose; Ng, Amanda; Winter, Georg E.; Krijgsveld, Jeroen (Cell chemical biology, 2025)
Targeted protein degradation (TPD) has emerged as a powerful strategy to selectively eliminate cellular proteins using small-molecule degraders, offering therapeutic promise for targeting proteins that are otherwise undruggable. However, a remaining challenge is to unambiguously identify primary TPD targets that are distinct from secondary downstream effects in the proteome. Here we introduce an approach for selective analysis of protein degradation by mass spectrometry (DegMS) at proteomic scale, which derives its specificity from the exclusion of confounding effects of altered transcription and translation induced by target depletion. We show that the approach efficiently operates at the timescale of TPD (hours) and we demonstrate its utility by analyzing the cyclin K degraders dCeMM2 and dCeMM4, which induce widespread transcriptional downregulation, and the GSPT1 degrader CC-885, an inhibitor of protein translation. Additionally, we apply DegMS to characterize a previously uncharacterized degrader, and identify the zinc-finger protein FIZ1 as a degraded target.
Gesehen am 24.07.2025
Online verfügbar: 12 November 2024, Artikelversion: 16 Januar 2025